A Survey on Modern Online Ticket Booking Systems - Mr. A.N. Mhetre,; Mahesh Kadam,; Sahil Kalambe, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2024)
This study examines developments in the design and operation of online movie ticket booking systems and provides a thorough overview of the integration of secure QR code technologies, with a focus on visual cryptography. Although they make data access and exchange more efficient, QR codes are susceptible to risks such data tampering, counterfeiting, and unauthorized access. The use of visual cryptography to safeguard QR code data by splitting the code into discrete, unintelligible "shares" that must be combined in order to reconstruct the original data is the main topic of this survey. This study also examines advancements in ticketing platforms, particularly the move to frameworks like Node.js and MongoDB, which improve system scalability and performance. The findings show that data security, dependability, and user experience are much enhanced by contemporary encryption and backend developments in reservation systems.
Keywords: QR Code; Online Movie Ticket Booking System